Serum Homocysteine Is Associated With HDL Only in Stroke Patients With Small Vessel Occlusion - Kim, Yerim; Lee, Ju-Hun; Lee, Sang-Hwa; Kim, Yeo Jin; Kim, Chulho; Jang, Min Uk; Jung, San; Lim, Jae-Sung; Oh, Mi Sun; Yu, Kyung-Ho; Lee, Byung-Chul (Frontiers in Neurology, 2020)
Background: Although controversial, homocysteine (Hcy) and lipid parameters have been associated with particular stroke subtypes. However, there are limited studies concerning the relationship between Hcy and lipid levels in acute ischemic stroke (AIS). We evaluated the impact of Hcy levels on lipid profiles in terms of specific stroke subtypes. Methods: A total of 2324 patients with first-ever AIS were recruited from two hospitals in South Korea. The exclusion criteria were as follows: (a) prestroke modified Rankin scale (mRS) ≥ 1, (b) undetermined or other stroke etiology, and (c) absence of Hcy data. Among the 1580 eligible patients, the Hcy level was divided into tertile groups. Logistic regression was used to assess association of Hcy levels with lipid levels by stroke subtypes. Results: Significant downward trends in total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) were only observed in patients with small vessel occlusion (SVO) as Hcy increased. In logistic regression analysis, while in patients with SVO subtype, the highest level of Hcy tertiles (OR= 1.648, 95% CI=1.047-2.594) was associated with the lower HDL level (≤40 mg/dL), the significance disappeared in patients with LAA and CE subtypes. Conclusion: Although our study does not demonstrate causal relationship, we suggest that Hcy might play a mediating role between HDL and SVO stroke development. To clarify the role of Hcy on AIS, this study will provide academic support for designing future research.